2015
DOI: 10.1515/biolog-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic helminths in grey heron (Ardea cinerea) chicks

Abstract: Parasitological studies were carried out on pulli (n = 20) collected on a breeding colony near the W loc lawski Reservoir on the Vistula River (Central Poland). Larvae of the nematode Contracaecum rudolphii (mean intensity of infection 9.3) were detected in the stomachs of all chicks, with adult worms present in two chicks. Larvae of the nematode Porrocaecum ardeae (mean intensity 3.1), the tapeworm Paradilepis scolecina (58.5) and flukes of five genera: Tylodelphys, Posthodiplostomum, Apharyngostrigea, Paryph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Four other species recorded at Kranzloh and Tongrube ( P. scolecina, V. campylancristrota, M. xanthosomus and S. colymbi ) are all parasites of fish-eating birds. The adult stage of V. campylancristrota , for example, parasitizes herons (Kozicka, 1971), while cormorants are the main definitive host of P. scolecina (Dziekońska-Rynko & Dzika, 2011), though it is also known from the grey heron ( Ardea cinerea L., 1758) (Dziekońska-Rynko et al , 2015), and both S. colymbi and M. xanthosomus parasitize great crested grebes ( Podiceps cristatus L., 1758) (Sudarikov et al , 2006; Sitko & Heneberg, 2015). Sokolov et al (2015) recorded another parasite specific to herons, M. macrosphincter , on Chinese sleepers from Lake Bründlweiher.…”
Section: Discussionmentioning
confidence: 99%
“…Four other species recorded at Kranzloh and Tongrube ( P. scolecina, V. campylancristrota, M. xanthosomus and S. colymbi ) are all parasites of fish-eating birds. The adult stage of V. campylancristrota , for example, parasitizes herons (Kozicka, 1971), while cormorants are the main definitive host of P. scolecina (Dziekońska-Rynko & Dzika, 2011), though it is also known from the grey heron ( Ardea cinerea L., 1758) (Dziekońska-Rynko et al , 2015), and both S. colymbi and M. xanthosomus parasitize great crested grebes ( Podiceps cristatus L., 1758) (Sudarikov et al , 2006; Sitko & Heneberg, 2015). Sokolov et al (2015) recorded another parasite specific to herons, M. macrosphincter , on Chinese sleepers from Lake Bründlweiher.…”
Section: Discussionmentioning
confidence: 99%
“…This does not seem to be an isolated incident given that Fanke et al (2011) reported the death of three common crane, Grus grus Linnaeus (1758), due to intestinal perforation caused by severe infestation with this parasite. Species of the genus Porrocaecum Railliet & Henry, 1912 are cosmopolitan and present indirect life cycles; invertebrates serve as an intermediate host (ATKINSON et al, 2008;DZIEKONSKA-RYNKO et al, 2015). There are several records of P. ardeae regularly affecting birds of the families Gruidae and Ardeidae in Europe and Central America (SCHMIDT & NEILAND, 1973;HARTWICH, 1979; FANKE et al, 2011; DZIEKONSKA-RYNKO et al, 2015;SITKO & HENEBERG, 2015).…”
Section: Gastrointestinal Parasitesmentioning
confidence: 99%